Syndrome In Question - Fernanda Guedes Lavorato; Marcela Duarte Benez Miller; Daniel Lago Obadia; Natalia Solon Nery; Roberto Souto da Silva (Sociedade Brasileira de Dermatologia, 2014)
Brooke-Spiegler syndrome is an autosomal dominant disorder with variable penetrance and expression. It is characterized by a genetic predisposition to develop multiple adnexal neoplasias: cylindromas, trichoepitheliomas, and trichoblastomas. We describe a 54-year-old male patient with cylindromas, trichoepitheliomas, and trichoblastoma.